Trends of Temperature and Rainfall in Pokhara - Paudel, Upendra (Prithvi Academic Journal, 2020)
Climate is an average condition of temperature, humidity, air pressure, wind, precipitation and other meteorological elements. It is a changing phenomenon. Natural processes and human activities have helped change the climate. Temperature is a vital element of climate, which fluctuates in the course of time and leads to change other elements of the whole climate. An attempt has been made to analyze the pattern of temperature and rainfall of Pokhara with the help of the two decades’ temperature and rainfall conditions obtained from the station of Pokhara airport. The increasing trend of temperature and the decreasing trend of rainfall might be the symbol of climatic modification. This trend refers to some changes in the climatic condition that may affect water resources, vegetation, forests and agriculture.